Pete the cat : I love my white shoes - Litwin, Eric.; Dean, James, 1957- ([Taipei, Taiwan] : The Eastern Pub. Co., Ltd, 2013)
Pete the Cat wears his new white shoes while walking down the street, and as he steps into piles of strawberries, blueberries, and other messes--and the color of his footwear changes--he keeps on moving and singing to himself without being bothered.
K-3
Text in traditional Chinese.
Translated from the English.
Title taken from page facing t.p.; title on t.p. is in traditional Chinese characters.
Keywords: Cats -- Juvenile fiction; Shoes -- Juvenile fiction; Singing -- Juvenile fiction; Cats -- Fiction; Chinese language materials; Shoes -- Fiction; Singing -- Fiction; Stories in rhyme; Cats -- Fiction; Chinese language; Shoes -- Fiction; Singing -- Fiction; Stories in rhyme; Picture books for children